Constructing light-weight polar boron-doped carbon nitride nanosheets with increased active sites and conductivity for high performance lithium-sulfur batteries. (26th May 2020) - Jiang, Rujia; Jiang, Min; Huang, Zhongyuan; Wang, Juan; Kuang, Yafei; Fu, Chaopeng
Abstract: Lithium-sulfur (Li-S) batteries are highly attractive as one of the most promising energy storage systems owing to their superior theoretical capacity, low cost and environmental compatibility. Nevertheless, the low utilization of active materials and detrimental shuttle reactions severely inhibit the practical application of Li-S batteries. Herein, a lightweight 2D boron doped g-C3 N4 nanosheets (BCN) with abundant active sites and increased conductivity prepared by a facile route is introduced onto commercial separators to achieve high performance Li-S batteries. The prepared BCN displays a 2D thin layer nanosheet structure with a thickness of ～2.5 nm. The boron doping not only can increase surface area and improve electrical conductivity, but also chemically anchor more polysulfides due to the formed B-N bond, which can effectively minimize the shuttling of polysulfides through the synergistic effect of physical yield and chemical confinement. As a result, the assembled Li-S batteries employing BCN separators with multifunction display large discharge capacity of 1197 mAh g −1, high sulfur utilization and outstanding durability with a capacity decay rate of 0.09% per cycle at 1 C after 500 cycles, which are also supported by the density functional theory simulation. Additionally, the alleviated self-discharge behavior and good areal capacity (up to 6.4 mAh cm −2 ) at a high sulfur loading of the cell are also demonstrated. The exploration of BCN modified separator furnishes a viable way to construct high energy density and long lifespan Li-S batteries. Graphical abstract: Image 1 Highlights: B-doped C3 N4 nanosheets with abundant active sites and conductivity is prepared. Lightweight BCN can chemically anchor more polysulfides to minimize shuttle effect. The Li-S battery with BCN displays large capacity and outstanding durability. The results are also supported by the density functional theory simulation.